2008
DOI: 10.1002/rcm.3737
|View full text |Cite
|
Sign up to set email alerts
|

Travelling wave ion mobility mass spectrometry studies of protein structure: biological significance and comparison with X‐ray crystallography and nuclear magnetic resonance spectroscopy measurements

Abstract: The three-dimensional conformation of a protein is central to its biological function. The characterisation of aspects of three-dimensional protein structure by mass spectrometry is an area of much interest as the gas-phase conformation, in many instances, can be related to that of the solution phase. Travelling wave ion mobility mass spectrometry (TWIMS) was used to investigate the biological significance of gas-phase protein structure. Protein standards were analysed by TWIMS under denaturing and near-physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
213
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 166 publications
(232 citation statements)
references
References 22 publications
19
213
0
Order By: Relevance
“…There is now substantial evidence to support the view that the gas-phase protein structure can reflect, under controlled conditions, the native solution-phase structure [1,6,12]. Multiple studies have shown good agreement between rotationally averaged cross-sectional measurements obtained from X-ray and NMR structures and those obtained by ion mobility experiments [7,[13][14][15][16][17].…”
mentioning
confidence: 92%
See 3 more Smart Citations
“…There is now substantial evidence to support the view that the gas-phase protein structure can reflect, under controlled conditions, the native solution-phase structure [1,6,12]. Multiple studies have shown good agreement between rotationally averaged cross-sectional measurements obtained from X-ray and NMR structures and those obtained by ion mobility experiments [7,[13][14][15][16][17].…”
mentioning
confidence: 92%
“…There is now substantial evidence to support the view that the gas-phase protein structure can reflect, under controlled conditions, the native solution-phase structure [1,6,12]. Multiple studies have shown good agreement between rotationally averaged cross-sectional measurements obtained from X-ray and NMR structures and those obtained by ion mobility experiments [7,[13][14][15][16][17].In this study traveling-wave ion mobility mass spectrometry (TWIMS) was used to probe the gasphase conformations of hemoglobin tetramers and their constituents.Address reprint requests to Dr. …”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Recent years have witnessed the rapid growth of traveling wave (TW) IMS, where ions Bsurf^on DC waves within a stacked-ring rf ion guide [31,[49][50][51]. It has been found empirically [52] that t d in TWIMS is related to Ω according to…”
Section: Introductionmentioning
confidence: 99%